2019
DOI: 10.1038/s41598-019-53444-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic analysis of defensive responses of Brassica juncea – B. fruticulosa introgression lines to Sclerotinia infection

Abstract: Sclerotinia stem rot caused by Sclerotinia sclerotiorum is a major disease of crop brassicas, with inadequate variation for resistance in primary gene pools. We utilized a wild Brassicaceae species with excellent resistance against stem rot to develop a set of B. juncea - B. fruticulosa introgression lines (ILs). These were assessed for resistance using a highly reproducible stem inoculation technique against a virulent pathogen isolate. Over 40% of ILs showed higher levels of resistance. IL-43, IL-175, IL-215… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 71 publications
1
26
1
Order By: Relevance
“…fruticulosa, where highly resistant plants with lesion sizes less than 2.5 cm were recorded (Rana et al, 2017). Atri et al (2019) identified 13 loci responsible for S. sclerotiorum resistance on seven different B. juncea chromosomes that were used in the set of B. juncea-B. fruticulosa ILs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fruticulosa, where highly resistant plants with lesion sizes less than 2.5 cm were recorded (Rana et al, 2017). Atri et al (2019) identified 13 loci responsible for S. sclerotiorum resistance on seven different B. juncea chromosomes that were used in the set of B. juncea-B. fruticulosa ILs.…”
Section: Discussionmentioning
confidence: 99%
“…However, enormous genetic variations do exist in important agronomic traits, including disease resistance within the Brassicaceae family (Warwick, 1993). Camelina sativa, B. desnottesii, Capsella bursapastoris, Diplotaxis catholica, D. erucoides, D. tenuisiliqua, and S. alba are well documented for their resistance to Alternaria brassicae (Brun et al, 1988;Conn et al, 1988;Sharma et al, 2002), where S. alba, Erucastrum cardaminoides, E. abyssinium, B. fruticulosa, D. tenuisiliqua show resistance to Sclerotinia sclerotiorum (Li et al, 2009;Garg et al, 2010;Rana et al, 2017Rana et al, , 2019Atri et al, 2019). Out of these, S. alba was found to be the most promising due to its resistance to major biotic and abiotic diseases that affect rapeseed and mustard, such as Alternaria blight (Kolte, 1985;Brun et al, 1987;Ripley et al, 1992;Sharma and Singh, 1992;Earle, 1995, 1997;Sharma et al, 2002), Sclerotinia stem rot (Kolte, 1985;Li et al, 2009), blackleg, beet cyst nematode (Lelivelt et al, 1993), flea beetles (Bodnaryk and Lamb, 1991) heat, drought (Downey et al, 1975;Primard et al, 1988;Downey and Röbbelen, 1989;Brown et al, 1997;Kumari et al, 2018), and pod shattering (Downey, 1987;Chandler et al, 2005;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These NGS-based SNP genotyping approaches have been applied widely for the QTL mapping of disease resistance traits and identification of candidate genes through genome-wide association studies (GWAS) in Brassica crops ( Table 2 ). Highlights include the discovery of novel disease resistance QTLs/genes at an unprecedented speed, for example, in Blackleg [ 72 , 73 ], Sclerotinia [ 74 , 75 , 76 ] and Clubroot [ 77 , 78 , 79 ]. The other benefit of the application of NGS-based SNP genotyping is the successful breeding of B. napus varieties containing multiple improved traits.…”
Section: Application Of Omics Technologies In Brassica mentioning
confidence: 99%
“…However, recently, qualitative cotyledon resistance has been demonstrated in B. juncea genotypes Ringot I and Seeta (Ge et al, 2015) and also in some interspecific crosses involving B. juncea (Barbetti et al, 2014). Perhaps of most significance are the studies by Rana et al (2017) and Atri et al (2019) (Gaur et al, 2016). In Australia, the B. juncea genotypes tested to date are all very susceptible to sclerotinia (Uloth et al, 2015b).…”
Section: Sclerotinia Stem Rotmentioning
confidence: 99%
“…Introgression from other brassicas, such as B. carinata (Barbetti et al, 2014), three wild crucifers (E. cardaminoides, Diplotaxis tenuisiliqua, and Erucastrum abyssinicum; Garg et al, 2010a) and most recently B. fruticulosa (Rana et al, 2017;Atri et al, 2019) and again E. cardaminoides (Rana et al, 2019), has also been performed to develop resistant B. juncea cultivars by interspecific hybridization.…”
Section: Sclerotinia Stem Rotmentioning
confidence: 99%